VIth World Congress on Science and Football, Book of Abstracts, January 16-20, 2007, Antalya, Turkey - Poster Presentations - Nutrition (Journal of Sports Science & Medicine, 2007)
Summaries on the following topics: P-074 Lifestyles and nutritional habits of footballers from North Cyprus Football League P-075 Effects of nutrition patterns in soccer players P-076 Nutrition before, during and after soccer P-077 Fluid and electrolyte requirements of soccer players P-078 Soccer and nutrition P-079 Yo-Yo intermittent recovery test in a young soccer team of Brazil before and after protein supplementation plus carbohydrate P-080 Relationship of pre-match hydration status to match performance, injury and body mass changes in elite Australian Rules Football P-081 Effects of creatine supplementation on speed in soccer